The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.01.11.426183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heme auxotrophy in abundant aquatic microbial lineages

Abstract: Heme, a porphyrin ring complexed with iron, is a metalloprosthetic group of numerous proteins involved in diverse metabolic and respiratory processes across all domains of life, and is thus considered essential for respiring organisms1,2. Several microbial groups are known to lack the de novo heme biosynthetic pathway and therefore require exogenous heme from the environment3. These heme auxotroph groups are largely limited to pathogens4,5, symbionts6,7, or microorganisms living in nutrient-replete conditions8… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, lack of heme biosynthesis in free-living organisms is considered extremely rare. Challenging this long-standing belief, a recent screen of more than 24,000 bacterial genomes (GTDB database r95) showed that heme auxotrophy is in fact highly prevalent across many ubiquitous bacterial groups found in freshwater habitats (Kim et al, 2021). Another study supporting this also detected the presence of nanomolar levels of the iron(III) protoporphyrin IX (heme precursor)-like compounds in natural estuarine water bodies (Vong et al, 2007).…”
Section: Non-canonical Roles Of Shared Bioenergetic Machinerymentioning
confidence: 99%
“…However, lack of heme biosynthesis in free-living organisms is considered extremely rare. Challenging this long-standing belief, a recent screen of more than 24,000 bacterial genomes (GTDB database r95) showed that heme auxotrophy is in fact highly prevalent across many ubiquitous bacterial groups found in freshwater habitats (Kim et al, 2021). Another study supporting this also detected the presence of nanomolar levels of the iron(III) protoporphyrin IX (heme precursor)-like compounds in natural estuarine water bodies (Vong et al, 2007).…”
Section: Non-canonical Roles Of Shared Bioenergetic Machinerymentioning
confidence: 99%
“…In some monoderm bacteria, the terminal heme biosynthesis enzyme coproheme decarboxylase (ChdC) and other enzymes of the CPD are found, but the CPD does not appear to be the predominant heme biosynthesis pathway across these phyla. In the Chloroflexota, for example, combinations of enzymes of the protoporphyrin dependent pathway (PDP), Siroheme and CPD pathways are found, with some species having enzymes from all three pathways (Kim et al, 2021). Though several genomes have the terminal heme synthesis enzyme coproheme decarboxylase (ChdC see Figure 1), no species that have been found to have a complete heme biosynthesis pathway utilizes only the CPD pathway (Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the Chloroflexota, for example, combinations of enzymes of the protoporphyrin dependent pathway (PDP), Siroheme and CPD pathways are found, with some species having enzymes from all three pathways (Kim et al, 2021). Though several genomes have the terminal heme synthesis enzyme coproheme decarboxylase (ChdC see Figure 1), no species that have been found to have a complete heme biosynthesis pathway utilizes only the CPD pathway (Kim et al, 2021). The first enzyme unique to the CPD, coproporphyrinogen III oxidase (CgoX see Figure 1), and the last, ChdC, have also been found in multiple bacteria of the Deinococcota, suggesting that the CPD may be utilized by these bacteria, though further studies are needed to verify that heme is synthesized via this pathway (Dailey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%